2002
DOI: 10.1029/2000jd000229
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐aerosol relationships of H2SO4, MSA, and OH: Observations in the coastal marine boundary layer at Mace Head, Ireland

Abstract: [1] Atmospheric concentrations of gaseous sulfuric acid (H 2 SO 4 ), methane sulfonic acid (MSA), and hydroxyl radicals (OH) were measured by chemical ionization mass spectrometry (CIMS) during the second New Particle Formation and Fate in the Coastal Environment (PARFORCE) campaign in June 1999 at Mace Head, Ireland. Overall median concentrations in marine background air were 1.5, 1.2, and 0.12 ϫ 10 6 cm Ϫ3 , respectively. H 2 SO 4 was also present at night indicating significant contributions from nonphotoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
159
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(179 citation statements)
references
References 61 publications
15
159
4
1
Order By: Relevance
“…Thus our model predicts that under some atmospheric conditions, particle formation from MSA should be similar in magnitude to that from sulfuric acid, as indicated by the field measurements (37,38). It is noteworthy that this consistency between the model predictions and field results arises even though atmospheric concentrations of MSA are typically ppt (28,32), as assumed in the model calculations, rather than ppb, which is experimentally accessible in our system. Once new particles have been formed from MSA, they can then grow by uptake of low and semivolatile gases formed in other atmospheric processes.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus our model predicts that under some atmospheric conditions, particle formation from MSA should be similar in magnitude to that from sulfuric acid, as indicated by the field measurements (37,38). It is noteworthy that this consistency between the model predictions and field results arises even though atmospheric concentrations of MSA are typically ppt (28,32), as assumed in the model calculations, rather than ppb, which is experimentally accessible in our system. Once new particles have been formed from MSA, they can then grow by uptake of low and semivolatile gases formed in other atmospheric processes.…”
Section: Discussionmentioning
confidence: 55%
“…Although it is known that ammonia and amines enhance particle formation from sulfuric acid (14-19, 29, 30), the effect of amines on MSA chemistry has not been reported. Their impact on atmospheric particle formation could be important, given that there are many sources of amines in air (31) and gas-phase MSA is typically 10-100% of that of gas-phase H 2 SO 4 in the coastal marine boundary layer (32,33). MSA is commonly detected in atmospheric particles (34-36), and particulate methanesulfonate, dimethylamine (DMA), and cloud condensation nuclei (CCN) activity have been observed to be highly correlated (36).…”
mentioning
confidence: 99%
“…These observations also showed that [H 2 SO 4 ] values typically were at the 10 6 -10 7 cm −3 range at noon, depending on the season. There are also measurements that have shown that [H 2 SO 4 ] can be at the 10 8 cm −3 range in the polluted environment [Bardouki et al, 2003;Berresheim et al, 2002]. While these studies were mostly ground-based or in the boundary layer, H 2 SO 4 measurements also exist for the free troposphere [Clarke et al, 1998;Weber et al, 1998] and for the upper troposphere and lower stratosphere [Lee et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…However, in coastal areas, sulfuric acid does not correlate with new particle formation or tidal cycles. [1,2] The measurement of iodine in the ultrafine particle composition [3] during coastal nucleation events has focused attention on organic and inorganic emissions from seaweed as potential iodine sources. Molecular iodine [4] and CH 2 I 2 [5] are likely precursors, since they rapidly photolyze to give iodine atoms, which are converted to the IO radical by reaction with ozone.…”
mentioning
confidence: 99%